2018
DOI: 10.1016/j.jtcvs.2018.02.101
|View full text |Cite
|
Sign up to set email alerts
|

Partial thromboplastin time is more predictive of bleeding than anti-Xa levels in heparinized pediatric patients after cardiac surgery

Abstract: In heparinized pediatric patients after cardiac surgery, increased risk of bleeding is more closely associated with elevated aPTT levels than elevated anti-Xa levels. In addition to anti-Xa, monitoring of aPTT levels should be considered during titration of UFH in pediatric patients after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…10 Based on a previous study, our center utilizes a combination of PTT and anti-Xa levels to adjust UFH dosing. 17,18 Modifications of high dose goals may reduce the risk of bleeding in patients undergoing therapy with high-dose UFH.…”
Section: Discussionmentioning
confidence: 99%
“…10 Based on a previous study, our center utilizes a combination of PTT and anti-Xa levels to adjust UFH dosing. 17,18 Modifications of high dose goals may reduce the risk of bleeding in patients undergoing therapy with high-dose UFH.…”
Section: Discussionmentioning
confidence: 99%
“…However, available studies indicated that aPTT was neither sensitive nor specific to define coagulation dysfunction. [21][22][23][24][25][26][27][28][29][30][31] The presence of DIC was also considered. However, although current definitions of DIC vary, all are ultimately based on laboratory parameters that have been included in our proposed criteria for coagulation dysfunction.…”
Section: D-dimermentioning
confidence: 99%
“…The serum anticoagulant activity can be measured by the standard plasma clotting time assays. The deviation from the normal ranges for APTT and PT suggest coagulation aberrations that may lead to bleeding disorders [23,24]. The analyses of chemical pathological parameters turned out variations in these parameters as well.…”
Section: Discussionmentioning
confidence: 98%